Reliability, validity, and acceptability of the simplified Mandarin Chinese EORTC QLQ-OPT30 for uveal melanoma patients - Yonghui Huang; Panpan Cui; Guangyan Dong; Tongfang Fan (Scientific Reports)
Abstract This study aimed to translate the EORTC QLQ-OPT30 into Mandarin (Simplified) Chinese and assess its reliability, validity, and acceptability among Chinese uveal melanoma (UM) patients. From January 2023 to June 2024, 60 UM patients from a tertiary hospital in central China were enrolled. The process involved both forward and back translation to develop the Mandarin (Simplified) Chinese version of the EORTC QLQ-OPT30. Statistical analyses were conducted using SPSS 25.0. Reliability was evaluated using Cronbach’s α coefficient, and validity was assessed through factor analysis and Pearson correlation tests. Acceptability was determined based on response rate and average completion time. The EORTC QLQ-OPT30 module contains 26 items for all patients, with an additional 4 items for those undergoing treatments other than enucleation. The module measures various aspects such as ocular irritation, visual impairment, headaches, concerns about disease recurrence, appearance issues, functional problems related to vision impairment, reading difficulties, functional issues in the treated eye, and driving problems. The study included 60 patients (45% male, 55% female) with an average age of (55.22 ± 10.02) years. The internal consistency reliability of the multi-item scales was acceptable, with Cronbach’s α values ranging from 0.848 to 0.946, except for the AP dimension, which had a lower α value of 0.567. The Mandarin (Simplified) Chinese version of the EORTC QLQ-OPT30 was tested in internal consistency, the split-half, and retest reliability, along with structural, convergent, and discriminant validity; as well as acceptability by its effectiveness, all the above demonstrated good values, making it a valuable tool for measuring health-related quality of life in Chinese UM patients.